DERMATAN SULPHATE PREVENTS VENOUS THROMBOSIS IN RATS WITHOUT INCREASING BLEEDING - Maggi, A; Abbadini, M; Salemi, R; Pangrazzi, J; Pagella, P G; Donati, M B (Thrombosis and Haemostasis, 1987)
Studies have suggested that endogenous proteoglycans, structurally similar to heparin, contribute to the “non-thrombogenicity” of the vascular wall. Our studies concentrated on Dermatan Sulphate (DS-MF 701) Heparin Sulphate (HS) and Standard Heparin (SH), all from Mediolanum Farmaceutici. The antithrombotic potential of these GAGs was evaluated in a well established model of venous thrombosis consisting in the ligature of the vena cava, 15 min after i.v. administration of the drug. A dose response-curve was obtained for DS (0.25-4 mg/kg), HS (1 -5 mg/kg) and SH (0.5-2 mg/kg).At the dose of 2 mg/kg DS was able to inhibit thrombotic occurrence by 80%, as compared to heparin 100% and HS 40%. The haemorrhaglc potential of these GAGs was then evaluated using two in vivo tests, the “template” method, which detects any alterations in primary haemostasis, and the tail “transection” method which is not only sensitive to changes in primary haemostasis but also to coagulation and fibrinolytic abnormalities; the tests were carried out 15 min after drug administration. Unlike SH, DS did not induce bleeding at equipotent antithrombotic doses wheareas HS induced bleeding even if not to the same extent as SH. DS did not modify the coagulation tests (APTT, TT and anti-Xa), again unlike SH. In conclusion, DS in the venous thrombosis model used, showed the peculiarity to prevent thrombus formation without inducing bleeding complications.